1986
DOI: 10.1038/bjc.1986.15
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of bleomycin, hyperthermia and a calmodulin inhibitor (trifluoperazine) in mouse tumour cells: Ii. DNA damage, repair and chromatin changes

Abstract: Summary We have reported in the preceding paper that the treatment of plateau phase mouse EMT6 tumour cells with a combination of hyperthermia (HT; 44°C) and trifluoperazine (TFP; 30, an inhibitor of calmodulin) greatly enhances the cytotoxicity of the antitumour drug belomycin (BLM). The cytotoxic action of BLM is thought to arise from the induction of DNA damage in a manner which reflects chromatin accessibility. Thus we have studied the effects of the two modifiers (HT and TFP) on chromatin structure and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In this respect, prior measurements have demonstrated that CaM and histone H2AX interact to form a protein complex that dissociates upon cellular exposure to high doses of radiation , suggesting a possible functional involvement for CaM in promoting DNA repair. Alternatively, CaM may act to diminish rates of DNA damage through a variety of mechanisms that either reduce rates of reactive oxygen species generation or act to promote alterations in chromatin structure to diminish the sensitivity of DNA to oxidative damage ,, .…”
Section: Resultsmentioning
confidence: 99%
“…In this respect, prior measurements have demonstrated that CaM and histone H2AX interact to form a protein complex that dissociates upon cellular exposure to high doses of radiation , suggesting a possible functional involvement for CaM in promoting DNA repair. Alternatively, CaM may act to diminish rates of DNA damage through a variety of mechanisms that either reduce rates of reactive oxygen species generation or act to promote alterations in chromatin structure to diminish the sensitivity of DNA to oxidative damage ,, .…”
Section: Resultsmentioning
confidence: 99%
“…There is abundant information indicating that the chromosomal sensitivity of mammalian cells to clastogenic compounds is closely related with the chromatin fibril structure [Kuo and Hsu, 1979;Kuo, 1981;López-Larraza and Bianchi, 1993;Smith et al, 1986]. Recently, we analyzed the sensitivity to SN of CHO chromosomes substituted with different halogenated compounds and found that DNA substitution with BrdUrd or IdUrd potentiates the chromosome damage induced by the antibiotic.…”
Section: Discussionmentioning
confidence: 99%
“…BLM induces a spectrum of DNA modifications that comprise alkali-sensitive lesions, ssDNA breaks, and dsDNA breaks in a proportion of 5:5:1 (Smith et al. 1986).…”
Section: Discussionmentioning
confidence: 99%